Integration of Higher Order Thinking Skills and Biological Literacy Among Students: A Gender Comparison Study - Gita Septi Rahmadwi; Iffa Ichwani Putri; Nurkhairo Hidayati; Nurul Fauziah; Sepita Ferazona; Andri Hendrizal (Universitas Syiah Kuala, in collaboration with the Perkumpulan Pendidik IPA Indonesia (PPII), (MoU), 2026)
Measuring biological literacy and higher order thinking skills (HOTS) is crucial, yet evidence on how assessment types and gender impact these competencies remains limited. Therefore, this study aims to analyze students’ integrated HOTS in biological literacy based on assessment types and gender. Employing a quantitative approach with a comparative design involving 129 11th-grade high school students, comprising 42 males and 87 females. The research instrument consisted of a biological literacy integrated HOTS test comprising 20 multiple-choice questions and 5 essay questions on the human digestive system. The instrument was validated by learning experts and biology subject experts, and its reliability was tested using Cronbach’s alpha. Data were analyzed using descriptive statistics and an independent samples t-test. The results showed the instrument was highly valid category (92.71%) and reliable (0.785 for multiple-choice questions and 0.780 for essay questions). Findings revealed that students’ HOTS achievement on multiple-choice questions (80.89) was higher than on essay questions (62.33). Additionally, a significant gender difference was found 0.041 (<0.05), where female students achieved a higher average HOTS score than male students. This study indicates that integrating HOTS with biological literacy through graphical representations, tables, and images can support the assessment of students’ analytical, evaluative, and creative thinking skills in biology learning